1988
DOI: 10.1104/pp.88.3.780
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Indole-3-Acetic Acid in Dark-Grown Seedlings of the Diageotropica and Epinastic Mutants of Tomato (Lycopersicon esculentum Mill.)

Abstract: ABSTRACIEndogenous indoleacetic acid (IAA) levels were examined in 7-dayold, dark-grown tomato seedlings (Lycopersicon esculentum Mill. cv VFN8), and in two single-gene mutants, Epinastic and diageotropica. Gas chromatography-mass spectrometry was employed to quantify IAA using '3C6-Ibenzene ringlindoleacetic acid as internal standard. IAA concentrations ranged from 89 to 134 nanograms per gram dry weight and were not significantly different for the three genotypes. Ethylene overproduction by dark-grown Epi se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0
2

Year Published

1989
1989
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 24 publications
0
26
0
2
Order By: Relevance
“…Ethylene production is also reduced in auxin-treated dgt tomato plants (Bradford and Yang, 1980;Kelly and Bradford, 1986). However, the rate of polar indole-3-acetic acid (IAA) transport in dgt hypocotyls and roots is similar to that of the WT parent (Daniel et al, 1989;Muday et al, 1995) and levels of IAA in dgt shoot apices were shown to be normal (Fujino et al, 1988). These results generally support the hypothesis that tomato dgt is altered in auxin perception or response.…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…Ethylene production is also reduced in auxin-treated dgt tomato plants (Bradford and Yang, 1980;Kelly and Bradford, 1986). However, the rate of polar indole-3-acetic acid (IAA) transport in dgt hypocotyls and roots is similar to that of the WT parent (Daniel et al, 1989;Muday et al, 1995) and levels of IAA in dgt shoot apices were shown to be normal (Fujino et al, 1988). These results generally support the hypothesis that tomato dgt is altered in auxin perception or response.…”
Section: Introductionmentioning
confidence: 54%
“…Phenotypic studies in tomato together with direct measurements of auxin concentration and transport suggested a role for DGT in auxin signaling rather than in auxin biosynthesis or transport (Fujino et al, 1988;Daniel et al, 1989;Muday et al, 1995). The tomato dgt mutants were established as a useful tool to study auxin signaling in tomato and in angiosperms in general.…”
Section: How Does Dgt Regulate the Auxin Response?mentioning
confidence: 99%
“…Most of the studies in tomato have focused on two mutants, dgt and epinastic (Ursin and Bradford, 1989;Muday et al, 1995). However, the phenotypic characteristics of each mutant are not a consequence of differences in the endogenous levels of IAA (Fujino et al, 1988). Tal and Imber (1970) proposed that another ABAdeficient mutant of RR, flacca, was higher in auxins as measured by the wheat-coleoptile bioassay.…”
Section: Dlscusslonmentioning
confidence: 99%
“…The dgt mutant exhibits horizontal growth habit, thin stems, hyponastic leaves, lack of lateral roots, reduced ethylene production, and insensitivity to auxin (Ursin and Bradford, 1989). The inability of auxin to induce growth in the dgt mutant apparently results from a defect in auxin-induced cell-wall loosening (Daniel et al, 1989), since the endogenous levels of IAA are the same in the mutant and wild-type parent (Fujino et al, 1988).…”
mentioning
confidence: 99%
“…Although endogenous levels of IAA are the same in the shoot tips of dgt and VFN8 (8), dgt mutants are nearly insensitive to exogenously applied auxin with respect to hypocotyl elongation and ethylene production (2,13). The Additional evidence supporting the notion that dgt and its isogenic parent, VFN8, provide a unique system to study auxin action stems from recent work (1 1) utilizing the photoaffinity auxin analog, 3H-5N3-IAA (azido-IAA).…”
mentioning
confidence: 99%